A predictive capability for the aerodynamic deformation of convertible car roofs - Knight, J; Lucey, Anthony; Shaw, C (Professional Engineering Publishing Ltd., 2010)
The flow-induced deformation of a membrane in a flow is studied using experimental and computational approaches in a configuration that represents the effect of the aerodynamic load on a convertible car roof. The computational method couples a commercial computational fluid dynamics code with an in-house structural code to predict membrane deformation. A converged statically deformed state, within 1 per cent difference in the displacement variable, is reached after three iterations between the fluid and structural codes. The predictions of membrane deformation are shown to agree well with the experimental results. The key outcome is the demonstration of a methodology that will be useful in the engineering design of convertible car roofs